DEVELOPING GLOBAL COMPETENCIES IN CHEMISTRY EDUCATION AND LINKING THEM TO FUNCTIONAL SCIENTIFIC LITERACY (Web of Teachers: Inderscience Research, 2025)
This article explores the integration of global competencies into chemistry education and their connection to the development of functional scientific literacy. In today’s interconnected world, chemistry teaching must go beyond content delivery to equip learners with skills such as critical thinking, problem-solving, intercultural communication, and responsible decision-making. The study highlights how incorporating real-world problems, interdisciplinary contexts, and inquiry-based learning can foster global competencies in the chemistry classroom. By aligning chemistry curricula with international frameworks such as PISA and UNESCO’s global competence model, the article presents pedagogical strategies that help students apply scientific knowledge functionally in social, environmental, and technological contexts. The findings suggest that a global and competency-based approach to chemistry education enhances not only students’ subject mastery but also their readiness to address complex global challenges.